A re-assessment of age dating of fossiliferous limestones in eastern Sabah, Borneo: Implications for understanding the origins of the Indo-Pacific marine biodiversity hotspot - McMonagle, L.; Lunt, P.; Wilson, Moyra; Johnson, K.; Manning, C.; Young, J. (Elsevier Science BV, 2011)
On the basis of a combined larger benthic foraminifera, nannofossil and strontium isotope dating programme we confidently re-assign muddy carbonate deposits from the Lower Kinabatangan River Area of Borneo to the Oligocene rather than the Early Miocene. High-diversity, coral-rich (> 50 species) deposits are here tightly constrained to predominately at, or just after, the Early to Late Oligocene boundary (Larger benthic foraminifera zone — Te1, Nannofossil zone — NP24, Sr isotope ages — 28.8–27.6 Ma). This new dating potentially pushes back the start of the Indo-West Pacific Centre of Marine Diversity, at least for corals, about 5 million years earlier than previous data indicated. Our new data supports maintaining separation of the muddy carbonates (previously defined as the Lower Kinabatangan Limestones: Haile & Wong, 1965) from nearby crystalline limestones of the Gomantong Limestone Formation dated here as Early Miocene (Larger benthic foraminifera zone — Te5/earliest Tf1, Sr isotope age — 21.0 Ma).This apparently punctuated development of shallow marine carbonates is seen at several locations in northern Borneo; an area underlain by oceanic crust and long dominated by very deep marine sedimentation (Hutchison, 2005). The opportunistic formation of clastic-influenced coastal and isolated biohermal carbonates is both an important palaeontological data point and a geological marker of changing basin settings. The new data on the first shallow marine deposits in a long established deep marine location, and evidence for unconformities, has important implications for the regional tectonic model, in an area of hydrocarbon exploration.